Cross-Cultural Strategic Management Practices in Global Supply Chains - Brian, Brian (European Journal of Business and Strategic Management, 2025)
Purpose: The general objective of this study was to explore cross cultural strategic management practices in global supply chains. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to cross cultural strategic management practices. Preliminary empirical review revealed that cross-cultural strategic management practices were crucial for global supply chain effectiveness, enhancing communication, leadership, and decision-making. Companies that incorporated cultural intelligence experienced better cohesion and resilience, while those neglecting cultural factors faced inefficiencies. The study highlighted the need for standardized cultural frameworks, emphasizing culture as an underutilized strategic asset in global supply chain management. Unique Contribution to Theory, Practice and Policy: The Hofstede’s Cultural Dimensions Theory, Institutional Theory and Dynamic Capabilities theory may be used to anchor future studies on cross-cultural strategic management practices in global supply chains. The study recommended integrating cross-cultural competencies into strategic frameworks through leadership training, diverse teams, and adaptive technologies. It called for expanding strategic models to include cultural factors, promoting inclusive management structures, and advocating for policy support on cultural training.